Continuous tunability of refractive index contrast in LiNbO3 optical waveguides fabricated by high-vacuum vapor-phase proton exchange - Mihnea Raoul Sandu; Alicia Petronela Rambu; Laura Hrostea; Sorin Tascu (Scientific Reports)
Abstract The actual techniques allowing the fabrication of waveguides in lithium niobate are not able to satisfy one of the demands of modern integrated photonics namely the well-controlled tunability of index contrast over a large range of values (from high-index contrast to low index contrast). This paper presents a simple and reliable method allowing well-controlled index contrast tunability between high-index contrast (Δn e  = 0.1) and low-index contrast (Δn e  = 0.035) while benefiting from the optical nonlinearity of LiNbO3 waveguides fabricated using HiVac-VPE technique. The study involves both planar and channel lithium niobate waveguides. The planar waveguides subjected to an annealing process for 1 to 5.5 h, are characterized before and after the thermal treatment, in order to determine the index contrast evolution and to analyze the changes of index profile shapes. Furthermore, it is found that the index profile after annealing is fitted by an exponential function different from Gaussian fit found in well-known Annealed Proton Exchange technique. Additionally, the index contrast dependence of the annealing time is also fitted by an exponential function. Channel waveguides, fabricated in the same condition, were designed for single-mode propagation at telecom wavelength. After characterization, the best of investigated annealed channel waveguides exhibits propagation losses around 1.5 ± 0.1 dB/cm. Therefore, the presented technique offers the opportunity for customization of photonics circuitry, scalability of integrated photonics platform, enhancement of non-linear optical efficiency at the single photon level for quantum information platforms.